A consciência corporal na interpretação pianística - André, Sérgio da Silva (1992)
The present study was based on a substantive hypothesis, which anticipated that "it is important for the pianist, the knowledge of the potentialities of his body". The research was developed on a descriptive form by the analysis of the studied material, which proved to be reference for the following statement. It is been adopted, as an instrument of measurement, a questionary to search the opinions about the focused theme on the study, which has been answered by piano teachers, pianists, and students of piano in different levels of graduation. The main conclusion of the work, that embraces a series of preoccupations about the body conscience in piano-teaching-apprenticeship and in instrument execution, is this: Every activities in the quality of human beings, including the pianistic one, needs an effective performance by what we consider body, because being conscious of this same body, sends us to our interior, primeval, our total.